The influence of finely layered seabeds on acoustic propagation in shallow water - Duncan, Alec; Gavrilov, Alexander; Koessler, Matthew Walter (Australian Acoustical Society, 2014)
Except in the deep ocean, the seabed has a major influence on low-frequency acoustic propagation. The formulation of an adequate geoacoustic model of the seabed is therefore one of the most important tasks facing anyone carrying out acoustic propagation modelling to predict underwater sound levels in coastal and continental shelf waters. It is often assumed that seabed layering on scales significantly smaller than the acoustic wavelength can be ignored when carrying out such modelling, and that these layers can instead be replaced by a simplified model involving a small number of layers in which the geoacoustic parameters vary smoothly with depth. This paper explores this assumption, with particular reference to the finely layered elastic seabeds typical of the Australian continental shelf. This investigation is based on a comparison of the plane-wave reflection coefficient vs grazing angle curves of these two representations of the seabed.